2019
DOI: 10.12659/msm.916526
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of High Specific Volume Polysaccharide – A New Type of Dietary Fiber – On Molecular Mechanism of Intestinal Water Metabolism in Rats With Constipation

Abstract: Background The aim of this study was to evaluate the effects of a new type of dietary fiber – high specific volume polysaccharide (HSVP) – on fecal properties, serum vasoactive intestinal peptide (VIP) concentration, intestinal flora count, and expression of the VIP-cAMP-PKA-AQP3 signaling pathway. Marerial/Methods Compound diphenoxylate was used in 48 healthy Wistar rats to establish a constipation model. Rats were divided into a normal control group, a constipation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Regulating VIP-cAMP-PKA-AQP3 signaling pathway by active substances can inhibit constipation. 44 , 45 At the same time, the study also confirmed that Lactobacillus belongs to a probiotic bacteria, which can be used to regulate the function of the intestine, improve the internal environment of the intestine, regulate the balance of the intestinal microecology, promote the intestinal peristalsis function, and relieve constipation. 46 , 47 None of these studies have yet correlated the effects of probiotics on intestinal water metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…Regulating VIP-cAMP-PKA-AQP3 signaling pathway by active substances can inhibit constipation. 44 , 45 At the same time, the study also confirmed that Lactobacillus belongs to a probiotic bacteria, which can be used to regulate the function of the intestine, improve the internal environment of the intestine, regulate the balance of the intestinal microecology, promote the intestinal peristalsis function, and relieve constipation. 46 , 47 None of these studies have yet correlated the effects of probiotics on intestinal water metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…38 In addition, polysaccharide intervention could significantly increase the moisture content of cecal contents and decrease the hardness of intestinal contents, thereby shortening the emptying time of feces to relieve constipation. 39…”
Section: Resultsmentioning
confidence: 99%
“…Food & Function nal contents, thereby shortening the emptying time of feces to relieve constipation. 39…”
Section: Papermentioning
confidence: 99%
“…34 VIP stimulates intestinal peristalsis and promotes gastrointestinal motility. 35 ET maintains normal intestinal function by maintaining vascular tone and cardiovascular stability. 36 SS inhibits the release of gastrointestinal hormones and reduces the gastric emptying speed and smooth muscle contraction, thereby accelerating constipation.…”
Section: Discussionmentioning
confidence: 99%